Pewarisan fonem konsonan bahasa proto-austronesia dalam Bahasa Aceh dan Bahasa Jamee - Resi Syahrani Tausya; Dardanila Dardanila; Dwi Widayati (Universitas Lampung, 2023)
This study examines the inheritance of Proto-Austronesian consonant phonemes in Acehnese and Jamee languages. A qualitative descriptive method is employed, using observation and note-taking techniques for data collection. The analysis results indicate that the inheritance of consonant phonemes occurs in a linear and innovative manner, with similar distributions of phoneme changes in both languages. There are also more sporadic changes in consonant sounds. This research provides a deeper understanding of phonological evolution and interlanguage relationships within the Austronesian language family, serving as a basis for further investigations in historical linguistics. The limitations of this study include the limited data coverage restricted to Acehnese and Jamee languages, thus future research could involve other Austronesian languages and sociolinguistic factors to gain broader insights.Â Keywords: Inheritance, Proto-Austronesian, Acehnese, Jamee language, language evolution